A review of the turbine cooling fraction for very high turbine entry temperature helium gas turbine cycles for Generation IV reactor power plants - Gad-Briggs, Arnold; Pilidis, Pericles; Nikolaidis, Theoklis (ASME, 2016)
The potential for high Turbine Entry Temperatures (TET) turbines for Nuclear Power Plants (NPPs) require improved materials and sophisticated cooling. Cooling is critical to maintaining mechanical integrity of the turbine for temperatures >1000°C. Increasing TET is one of the solutions for improving efficiency after cycle optimum pressure ratios have been achieved but cooling as a percentage of mass flow will have to increase, resulting in cycle efficiency penalties. To limit this effect, it is necessary to know the maximum allowable blade metal temperature to ensure the minimum cooling fraction is used. The main objective of this study is to analyse the thermal efficiencies of four cycles in the 300 – 700 MW class for Generation IV NPPs, using two different turbines with optimum cooling for TETs between 950°C - 1200°C. The cycles analysed are Simple Cycle (SC), Simple Cycle Recuperated (SCR), Intercooled Cycle (IC) and Intercooled Cycle Recuperated (ICR). Although results showed that deterioration of cycle performance is lower when using improved turbine material, the justification to use optimum cooling improves the cycle significantly when a recuperator is used. Furthermore, optimised cooling flow and the introduction of an intercooler improves cycle efficiency by >3%, which is >1% more than previous studies. Finally, the study highlights the potential of cycle performance beyond 1200°C for IC. This is based on the IC showing the least performance deterioration. The analyses intend to aid development of cycles for deployment in Gas Cooled Fast Reactors (GFRs) and Very High Temperature Reactors (VHTRs).
Keywords: Molecular dynamics; single crystal silicon; anisotropy; cutting temperature